Mechanisms and Clinical Trials of Hepatocellular Carcinoma Immunotherapy - Huang, Shao-Li; Wang, Yu-Ming; Wang, Quan-Yue; Feng, Guang-Gui; Wu, Fu-Qing; Yang, Liu-Ming; Zhang, Xi-He; Xin, Hong-Wu (Frontiers in Genetics, 2021)
Hepatocellular carcinoma (HCC), one of the most common and lethal tumors worldwide, is usually not diagnosed until the disease is advanced, which results in ineffective intervention and unfavorable prognosis. Small molecule targeted drugs of HCC, such as sorafenib, provided only about 2.8 months of survival benefit, partially due to cancer stem cell resistance. There is an urgent need for the development of new treatment strategies for HCC. Tumor immunotherapies, including immune check point inhibitors, chimeric antigen receptor T cells (CAR-T) and bispecific antibodies (BsAb), have shown significant potential. It is known that the expression level of glypican-3 (GPC3) was significantly increased in HCC compared with normal liver tissues. A bispecific antibody (GPC3-S-Fabs) was reported to recruit NK cells to target GPC3 positive cancer cells. Besides, bispecific T-cell Engagers (BiTE), including GPC3/CD3, an aptamer TLS11a/CD3 and EpCAM/CD3, were recently reported to efficiently eliminate HCC cells. It is known that immune checkpoint proteins programmed death-1 (PD-1) binding by programmed cell death-ligand 1 (PD-L1) activates immune checkpoints of T cells. Anti-PD-1 antibody was reported to suppress HCC progression. Furthermore, GPC3-based HCC immunotherapy has been shown to be a curative approach to prolong the survival time of patients with HCC in clinically trials. Besides, the vascular endothelial growth factor (VEGF) inhibitor may inhibit the migration, invasion and angiogenesis of HCC. Here we review the cutting-edge progresses on mechanisms and clinical trials of HCC immunotherapy, which may have significant implication in our understanding of HCC and its immunotherapy.